Organisational justice, organisational identification and job involvement: the mediating role of psychological need satisfaction and the moderating role of person-organisation fit - Malhotra, N; Sahadev, S; Sharom, NQ (Routledge Journals, Taylor & Francis Ltd, 2024)
Indexed by WOS/SCOPUS/ERA